Energy security and sustainable economic growth in China - Yao, Shujie; Herrerias, Maria Jesus; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book focuses on various issues of energy, energy efficiency and environmental policy in China. It discusses different aspects on how China may maintain its fast economic growth through good management of energy consumption and development of various energy sources.
Keywords: Energy security -- China; Energy policy -- China; Economic development -- China -- Environmental aspects